"ON THE ORGANIZATION OFTHE EVER-ATLANTIC TREATY", "NORTH ATLANTIC ALLIANCE" (British Journal of Global Ecology and Sustainable Development, 2023)
This article is an attempt to answer the question of whether it is possible in the foreseeable future to become an organization of political cooperation on the basis of the North Atlantic Alliance. Despite the increased rhetoric of "politicization" of NATO at the turn of the 1980s and 1990s, neither the United States nor its European allies tookit seriously The "politicization" of the alliance as a possible option for the development of NATO, partly due to the lack of an adequate alternative to this institution in the military sphere. An analysis of current trends points to the increasing importance of military cooperation within NATO for the American leadership and the possibility of strengthening the alliance's position as an institution of transatlantic cooperation that contributes to ensuring security on a global scale.